2006
DOI: 10.1890/0012-9658(2006)87[1556:wneisp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Whole-System Nutrient Enrichment Increases Secondary Production in a Detritus-Based Ecosystem

Abstract: Although the effects of nutrient enrichment on consumer-resource dynamics are relatively well studied in ecosystems based on living plants, little is known about the manner in which enrichment influences the dynamics and productivity of consumers and resources in detritus-based ecosystems. Because nutrients can stimulate loss of carbon at the base of detrital food webs, effects on higher consumers may be fundamentally different than what is expected for living-plant-based food webs in which nutrients typically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
213
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(227 citation statements)
references
References 67 publications
11
213
3
Order By: Relevance
“…Most stream ecosystems are naturally nutrient limited, and small increases in a limiting nutrient can enhance primary production with cascading effects on consumers (Hart and Robinson 1990, Slavik et al 2004, Cross et al 2006. We found that nutrient levels were significantly enhanced in spring-fed rivers and probably contributed to increased invertebrate density at these sites.…”
Section: Invertebrate Densitymentioning
confidence: 68%
“…Most stream ecosystems are naturally nutrient limited, and small increases in a limiting nutrient can enhance primary production with cascading effects on consumers (Hart and Robinson 1990, Slavik et al 2004, Cross et al 2006. We found that nutrient levels were significantly enhanced in spring-fed rivers and probably contributed to increased invertebrate density at these sites.…”
Section: Invertebrate Densitymentioning
confidence: 68%
“…This was caused by wood and leaf litter standing crops twofold lower in the nutrient-enriched than in the reference stream, presumably a result of the disappearance of organic matter in the treatment stream due to faster decomposition rates brought about by elevated microbial activity during 5 years of enrichment (21,24). Increased fungal biomass buildup and nitrogen immobilization in plant litter following nutrient addition (24,25) resulted in an enhanced food quality for consumers and higher invertebrate biomass and production of some invertebrate groups in this stream (8,9,21). At the same time, the availability of detrital resources decreased, which should have an opposite effect on some consumers over longer periods (8).…”
Section: Discussionmentioning
confidence: 99%
“…BPOM and seston, which is derived from BPOM, are food resources for collector-gatherers/shredders and collector-filterers, respectively. Dissolved nitrogen can enhance the growth of microbes that colonize BPOM (Gulis et al 2004), resulting in high-quality BPOM (e.g., Cross et al 2006). A high quantity and quality of food resources may have the same function as high productivity (Yee and Juliano 2007), and thus promote an increase in community density, leading to an increase in taxonomic richness.…”
Section: Environmental and Inter-guild Effects On Regional Gradientsmentioning
confidence: 99%